Potential for monetisation and utilisation of wood raw material from pioneer tree species stands in the Czech Republic - Roman Dudík; Petra Palátová; Aleš Kůs; David Homolka; Andreas Nikodemus (Journal of Forest Science)
Pioneer tree species in the Czech Republic include birch, alder and aspen. From an economic point of view, birch seems to be the most promising. Greater use of timber from pioneer tree species in higher value-added products is currently limited by the low stocks of birch, alder and aspen in forest stands. A price survey was carried out in the Western Highlands region in the central part of the Czech Republic to obtain basic information on the prices of assortments of pioneer tree species. The prices of five assortments of raw timber were surveyed for the period 2019-2023. Very few of the prices of pioneer tree species were found for assortments of II and IIIC; these assortments are not actually produced and, therefore, not traded by the respondents. For the roundwood assortments (quality II, IIIAB), it cannot be clearly stated that any of the preparatory timber species (birch, alder, aspen) always achieved a higher price during the observed period. Only in 2023 was it possible to see higher prices for quality IIIAB assortments of alder. Birch of quality V had the highest price of the observed prices for this timber assortment for the pioneer tree species during the period under review. When using a system approach, considering the information on the prices of the timber assortments is also important for deciding on the optimal species composition of the regenerating forest stands. In the case of the Czech Republic's commercial tree species, this information is available at the national level. However, the situation is quite the opposite for the timber assortments of pioneer tree species, where information on their prices is completely lacking. This confirms the fact that the market for assortments of timber from pioneer tree species in the Czech Republic is basically non-existent, the main reason being the low volume of these assortments placed on the market.